2004
DOI: 10.1124/jpet.103.055376
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Δ9-Tetrahydrocannabinol and Methanandamide in CB1 Knockout and Wild-Type Mice

Abstract: Mice devoid of CB1 cannabinoid receptors (CB1Ϫ/Ϫ mice) provide a unique opportunity to further investigate the role of CB1 receptors in exocannabinoid and endocannabinoid effects. CB1Ϫ/Ϫ mice (N ϭ 18) and their wild-type littermates (CB1ϩ/ϩ mice; N ϭ 12) were placed in standard mouse operant chambers and trained to lever press under a fixed ratio 10 schedule of reinforcement. When stable lever press responding under the fixed ratio 10 schedule had been established, cannabinoids and noncannabinoids were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…Circling did not occur after mAEA administration (Järbe et al , 2003a. Similarly, mAEA rate decreases of lever pressing were also augmented by rimonabant, whereas such rate changes induced by Δ9-THC essentially were unaltered (Järbe et al 2003b; see also Baskfield et al 2004). To account for such findings, it has been suggested that cannabinoid ligands interact with CB 1 R/CB 2 R through different binding motifs and/or through non-CB 1 R/CB 2 R cellular targets including additional cannabinoid subtypes or cannabinoid-like receptors and involvement of vanilloid receptor (VR 1 ) mechanisms (Howlett 2004;Pacher et al 2006;Oz 2006 for reviews).…”
Section: Discussionmentioning
confidence: 85%
“…Circling did not occur after mAEA administration (Järbe et al , 2003a. Similarly, mAEA rate decreases of lever pressing were also augmented by rimonabant, whereas such rate changes induced by Δ9-THC essentially were unaltered (Järbe et al 2003b; see also Baskfield et al 2004). To account for such findings, it has been suggested that cannabinoid ligands interact with CB 1 R/CB 2 R through different binding motifs and/or through non-CB 1 R/CB 2 R cellular targets including additional cannabinoid subtypes or cannabinoid-like receptors and involvement of vanilloid receptor (VR 1 ) mechanisms (Howlett 2004;Pacher et al 2006;Oz 2006 for reviews).…”
Section: Discussionmentioning
confidence: 85%
“…In addition, mAEA (but not Δ 9 -THC) decreased rates of responding that were not antagonized by rimonabant in CB 1 R-deficient mice (Baskfield et al 2004), indicating that these behavioral depressant effects of mAEA are not mediated by CB 1 R. Wiley et al (2005) also reported that the degree of cross-tolerance in mice between Δ 9 -THC on the one hand and AEA, 2-methylAEA and O-1812 on the other hand, varied with the test (locomotor activity, antinociception, temperature, and catalepsy) employed to examine cross-tolerance. Although the neural mechanisms responsible for these varied effects are unclear, it is worth noting that vanilloid mechanism(s) do not seem important for the discriminative stimulus effects of CB 1 R agonists because (a) the TRPV1 antagonist capsazepine did not block the Δ 9 -THC-like effects of AEA (Solinas et al 2007a) and (b) the TRPV1 agonist O-1839 did not substitute for either Δ 9 -THC or O-1812 in rats discriminating between vehicle and either of these two CB 1 R agonists .…”
Section: Discussionmentioning
confidence: 88%
“…Thus, studies have shown that the CB 1 receptor antagonist SR141716A reduces alcohol intake (Arnone et al, 1997;Colombo et al, 1998;Rodriguez de Fonseca et al, 1999) and the motivation to consume alcohol in a progressive ratio paradigm in rats, while a CB 1 receptor agonist increased the motivation to consume alcohol alcohol in a progressive ratio paradigm . In addition, ethanol (0.5-2.0 g/kg) has been shown to decrease operant responding to a greater extent in CB 1 À/À mice than in wild-type mice, suggesting a possible role of CB 1 receptor in the rate disruptive effects of ethanol (Baskfield et al, 2004). Recently, we and others have shown that ethanol consumption and/or preference are decreased in CB 1 À/À mice generated on a CD1 background (Naassila et al, 2004) or a C57BL/6J background (Poncelet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%